Port Areas Planning and effects of Port-City Barrier - Bernardo Sánchez Pavón (European Regional Science Association (ERSA), 2004)
Nowadays, goods sea transport involves a penetration of port hinterlands towards inland, which leads to the need for the confluence of the different means of transport in the neighbourhoods of ports and, therefore, new available areas. In the same way, what happened in New York on Septmeber 11th , 2001 have led to exigencies of security measures, which demand new areas and more restrictions on access. From all this, it follows that relations between port and city, where it is placed, are difficult. The purpose of this essay is to analyse the problems that the coexistence between ports and cities is going through, and to propose solutions which could allow a suitable coexistence.
Keywords: 330